The Characteristic of Coal Oil From Catalytic Coal Gasification - Rika Damayanti; Susila Arita; Fitri Hadiah (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2019)
In this work, the catalytic gasification process of coal was studied at different operating temperatures and catalyst weights. The purpose of this study was to study the characteristics of coal oil produced through the gasification process using Nickel Molybdenum (NiMo) catalyst. The effect of adding NiMo catalyst with variations in weight of 0%, 5%, 10% and 15% for different gasification temperatures (375 – 385 °C, 430 – 440 °C, and 475 – 485 °C) were studied on coal with a calorific value of 6,400 kcal/kg. The process was done in fluidized bed reactor under atmospheric pressure and an air flow rate of 2 liters/minute was flow for 60 minutes. The results showed that NiMo is effective as a catalyst in the gasification of coal at 430 – 440 °C, the addition of 15% weight of catalysts produced coal oil with a yield of 9.35% and the composition of hydrocarbon consists of 59.75% of aromatics, 26.42% of aliphatics, and 7.34% of phenolics. Compared to coal oil without catalyst give a yield of 6.56% with 57.33% of aromatics, 17.44% of aliphatics, and 16.03% of phenolics. This showing that NiMo catalysts have a high selectivity to increase aromatic and aliphatic hydrocarbons in coal oil.